An unusual case of unplanned complex suicide. Issue 4 (2nd October 2017) - Zengın Eroglu, Meliha; Şahan, Ebru; Kıraz, Seda
ABSTRACT: Suicide is defined as using more than one method to induce death. Suicides are divided into simple and complex cases. A complex suicide is defined as the use of more than one method to induce death. The planning of several methods for inducing death further permits the classification of suicide into planned and unplanned. In planned type, two or more methods are applied simultaneously to make sure that death will occur. In unplanned type, a second method is just used if the first method is unsuccessful or painful. Less fatal methods like poisoning or cutting is combined with a second method which is usually more lethal like shooting, falling from a height, burning, or hanging. Here, we present a complex suicide case who is living despite using three suicide methods consecutively.